Genetics and Conservation of Plant Species of Extremely Narrow Geographic Range - Sofia Solórzano; Salvador Arias; Patricia Dávila (Diversity, 2016)
The endemic plant species with extremely narrow geographical range (<100 km2) often have few populations of small size and tend to be more vulnerable to extinction by genetic drift and inbreeding effects. For these species, we tested if intraspecific genetic diversity can be applied to identify conservation priorities. The biological model was Mammillaria albiflora—a Mexican cactus that numbers ~1000 individuals distributed in four nearby patches covering 4.3 km2. A total of 96 individuals were genotyped with 10 microsatellite loci to describe the genetic substructure and diversity. There is significant population substructure: the genetic diversity is distributed in three genetic neighbors and varies among the patches, the genotypes are not randomly distributed and three genetic barriers restrict the gene flow. The current population size is 15 times smaller than in the past. The restricted gene flow and genetic drift are the processes that have shaped population substructure. To conserve the genetic diversity of this cactus we recommend that two patches, which are not private property, be legally protected; to include M. albiflora in the Red List Species of Mexico in the category of extinction risk; and a legal propagation program may help to diminish the illegal harvesting.